OBJECTS OF FORENSIC IDENTIFICATION OF A PERSON - Kamoliddinova, Feruza Kamoliddin qizi; Aminjonov, Nurillo Qobiljon o‘g‘li (INTERNATIONAL CONFERENCES, 2023)
In the article, the strictly individualizing characteristics of a person, born or acquired in the course of life, can act as defining characteristics and signs. Individual characteristics and signs of a person can be divided into two groups. The first are static (immutable) features: features of bone structure, fingerprint, eye structure, genome, etc. The second is dynamic: the parameters of written speech, a person’s voice, his gait, etc.